(untitled) (World Bulletin of Public Health, 2024)
In the article, the viral etiology of acute herpetic stomatitis, which has the highest rate among oral mucosal diseases in children, visited the admission department of the Regional Children’s Multidisciplinary Medical Center and various departments modern methods of treatment of sick children who are being treated as a related disease are widely covered in . In the article, we divided the children who came to the reception department with acute herpetic stomatitis in different departments of the hospital into 2 groups. Local treatment measures were applied to first group, and local treatment with antiseptic agents was applied to the 2 groups and a comprehensive approach including red gel-neon laser treatment is recommended. A complex approach to the treatment of acute herpetic stomatitis is local treatment with antiseptic agents and laser therapy has shown its maximum effectiveness in a short time all the symptoms of illness in children: intoxication, mouth in the oral cavity the symptoms of the disease, aphthae disappeared, there was no recurrence of the disease, and it reduced the severe forms of the disease in a short time and restored the normal immunity in children in a short time.